Foeniculum vulgare from Spice to Pharma: Recent Advances in Its Medicinal Value, Bioactivities and Perspectives - Shilpa Debnath; Hardik Kumar; Alok Sharma (Tehran University of Medical Sciences, 2023)
Foeniculum vulgare Mill. (F. vulgare) belongs to the family Apiaceae with numerous medicinal and traditional applications. It has been widely used in South Asia as an important medicine for the treatment of many ailments. Different parts of F. vulgare, including seeds, leaves, aerial part and fruits, has been found to contain diverse phytochemicals such as anethole, fenchone, limonene, estragole, and p-coumaric acid. In particular, anethole and fenchone as the chief bioactives isolated from F. vulgare, have been proven to possess notable antioxidant, antitumor, carminative, diuretic, and galactagogue effects and is useful in amenorrhoea, dental decay and irritable bowel syndrome. This review summarizes the botanical activities, traditional uses, phytochemistry, and pharmacology of F. vulgare, along with the clinical studies to serve as the basis for further research and development on this medicinal plant.